Políticas de currículo em Matinhos-PR: a voz dos professores - Kempa, Sydnei Roberto (2011)
This study analyses the curriculum organization policies, in the context of the Education Department in the city of Matinhos, PR, from 2005 to 2009. The studies which are concerned to the curriculum are even more relevant to the understanding of the educational phenomenon, which has different aspects and is in constant evolution. The leitmotif of this work is the continuous change movement of the curriculum organization and its implications, mainly for the teachers. The basic question which guides this work is: How do teachers cope with the continuous changes in the curriculum organization? As a unique data source, and as the most involved professionals in the curriculum changing process, the teachers voices of sixteen teachers from the municipal education system have been listened to, through semi-structured interviews. The raw material of this study was constituted from the multidimensional perceptions emerged in the teachers testimonials. The preparation of the raw material for subsequent analysis was based on the Content Analysis by Bardin (1994). The construction of the analysis was based on the Critical Pedagogy. Authors involved with the curriculum field, as Apple, Sacristán, Perez Gómez, Lima, Ball, Popkewitz provided the data to understand how the most of the changings in the curriculum scope occur and how the teachers survive them. The results are the ascertainments of how the policies are implemented and the implications they produce